2020
DOI: 10.1109/access.2020.3029288
|View full text |Cite
|
Sign up to set email alerts
|

Multistep Deep System for Multimodal Emotion Detection With Invalid Data in the Internet of Things

Abstract: The Internet of Things (IoT) technologies such as interconnection and edge computing help emotion recognition to be applied in healthcare, smart education, etc. However, the acquisition and transmission processes may have some situations, such as lost signals and serious interference noise caused by motion, which affect the quality of the received data and limit the performance of IoT emotion detection. We collectively refer to these as invalid data. A multi-step deep (MSD) system is proposed to reliably detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…RecNet [58] MARN [59] GRU-MP/EVE [60] SibNet [61] SymSynAN [61] HRL [66] PickNet [69] E2E [70] RecNet(RL) [72] DPRN [73] Wei [74] B_4 RecNet [58] MARN [59] GRU-MP/EVE [60] SibNet [61] SymSynAN [61] HRL [66] PickNet [69] E2E [70] RecNet(RL) [72] DPRN [73] Wei [74] M 0 10 20 30 40 50 60 70…”
Section: Multimodal Speech Synthesis Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…RecNet [58] MARN [59] GRU-MP/EVE [60] SibNet [61] SymSynAN [61] HRL [66] PickNet [69] E2E [70] RecNet(RL) [72] DPRN [73] Wei [74] B_4 RecNet [58] MARN [59] GRU-MP/EVE [60] SibNet [61] SymSynAN [61] HRL [66] PickNet [69] E2E [70] RecNet(RL) [72] DPRN [73] Wei [74] M 0 10 20 30 40 50 60 70…”
Section: Multimodal Speech Synthesis Resultsmentioning
confidence: 99%
“…RecNet [58] MARN [59] GRU-MP/EVE [60] SibNet [61] SymSynAN [61] HRL [66] PickNet [69] E2E [70] RecNet(RL) [72] DPRN [73] Wei [74] R 0 10 20 30 40 50 60…”
Section: Multimodal Speech Synthesis Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies generated machine learning models from 1039 noisy IoT data, and the models could achieve high accuracy 1040 [73], [74]. In contrast, studies on differential privacy showed 1041 that if the value of the privacy budget is small, i.e., if the 1042 noise added using differential privacy techniques is large, 1043 the accuracy of machine learning models will deteriorate 1044 significantly [53]- [55].…”
Section: B Machine Learning With Noisy Iot Data 1038mentioning
confidence: 99%